Are Foreign Banks in China Homogenous? : Classification of their Business Patterns - Yamaguchi, Masaki (Journal of Accounting, Business and Finance Research, 2018)
This study investigates the differences in the business patterns of foreign banks in China. Most previous studies examined the Chinese banking sector in the light of bank efficiency. This study sheds new light on foreign banks’ activities. We investigate 30 foreign banks in China using detailed financial data collected in 2016. This investigation uses non-hierarchical X-means clustering, as this method automatically presents an optimal number of clusters and sorts the foreign banks into their appropriate clusters. The X-means clustering method indicates three business patterns among foreign banks. It also characterizes respective clusters and demonstrates that several banks are oriented toward localization strategies. Other banks focus on security investments and the rest depend on both interbank loans and loans including corporate loans.